Communication-based interventions for increasing influenza vaccination rates among Aboriginal children: A randomised controlled trial. Issue 45 (29th October 2018) - Borg, Kim; Sutton, Kim; Beasley, Megan; Tull, Fraser; Faulkner, Nicholas; Halliday, Justin; Knott, Cameron; Bragge, Peter
Abstract: Background: In Australia, the influenza vaccine is funded for Aboriginal and Torres Strait Islander (hereafter referred to as Aboriginal) children aged 6 months to <5 years old. In Victoria, only 2% of Aboriginal children are vaccinated against influenza. Objective: To evaluate whether sending a letter or sending a pamphlet directly to parents/guardians would improve influenza vaccine uptake amongst Aboriginal identified children. Design: The study involved a multi-arm, parallel, randomised controlled trial with two intervention groups and one control group. Participants & setting: Participants included parents or guardians of Victorian children (aged 6 months to <5 years) who identified as Aboriginal. Households (n = 5534) were randomised (using a random number generator) to receive either a personalised letter (n = 1845), a pamphlet (n = 1845), or no direct communication (control) (n = 1844). The letter and the pamphlet were designed using the INSPIRE framework – a set of behaviour change techniques for action-oriented communication. Main outcome measure: The proportion of households where all eligible children received the influenza vaccine between 2 May 2017 and 1 September 2017. Results: The control group's vaccination rate was 4.4%, higher than previous years. The pamphlet group achieved a similar vaccination rate (4.5%). The letter group's vaccination rate of 5.9% was significantly higher than the control group [χ 2 (1, n = 3689) = 4.33, p = .037]. Conclusions: Sending a personalised letter directly to parents/guardians was an effective strategy for increasing influenza vaccination among Aboriginal children. The ineffectiveness of the pamphlet may be due to the lack of personalisation and the authority associated with the letter. Additional research is required to understand participant responses to the material. Trial registration: This research was retrospectively registered with the Australian New Zealand Clinical Trials Registry (ANZCTR) on 13 September 2017 (ACTRN12617001315303).